Performance Evaluation for Network Set up and Nodes Discovery Protocol in Underwater Grid Topology Networks - Othman, A.K.; Wan Zainal Abidin, W.A; Zen, H.; Hong Ping, Kismet Anak; Zamhari, N. (IEEE, 2010)
There has been a large volume of research invested over the last decade into overcoming the difficulties inherent with propagation of information bearing signals through the underwater acoustic communications. This has been driven by an increasing demand for reliable and high capacity Underwater Acoustic Networks (UANs). Applications of interest in this area include oceanographic information gathering, environmental monitoring and coastal defence. One of the major challenges in the UANs area of research is the development of a networking protocol that can cope with the adverse underwater environment. We proposed a scheme to perform node discovery based on time of arrival by only one seed node (Primary Seed) placed in known position. The primary seed is capable of determining neighbouring nodes and eventually all nodes in the network without GPS. The protocol of discovery and algorithms of selecting the next seed node that is capable of node discovery and gain their connectivity are suggested. In this paper the structured grid topology networks is used to compare and evaluate the performances of the algorithms. By the end of node discovery, each node will have the knowledge of nodes identification; number of nodes in the network and direction all other nodes.